Dinâmicas de desenvolvimento da piscicultura e políticas públicas no Vale do Ribeira/SP e Alto Vale do Itajaí/SC - Brasil - Silva, Newton José Rodrigues da [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Our study aims at understanding the relationships between public policies and freshwater fish aquaculture within the Ribeira watershed and the higher watershed of Itajai (Brazil). The theoretical framework lies on public policies evaluation, local innovative system and, sociology of translation. The methodology takes advantage of official documents, newspapers, interviews of key stakeholders and surveys through questionnaires. Trajectories of aquaculture together with territories occupation are described and analysed synchronically. Aquaculture dynamics are described by referring to a local innovative system integrating four poles of competency (production, training, science and financing) that can be assimilated to a socio-technical network. This study confirms our assumption: the ability of fish aquaculture is determined by the interaction between the four poles and public policies. The on-going dynamics of these interactions is crucial to make these activities sustainable. Within the Ribeira watershed, the interactions between the stakeholders of the network were mainly commercial. Government actions were primarily carried out for infrastructures and outside any socio-technical network, which weakened the ability to react when economic crises occurred in aquaculture. Within the Itajai higher valley, government actions were mainly focused on research and training interacting with a significant organization of stakeholders based on their cultural, geographical and social proximity. This situation gave them a higher ability to react when facing crises and to facilitate sustainability of aquaculture

O presente estudo tem como objetivo compreender a relação existente entre as políticas públicas e o desenvolvimento da piscicultura no Vale do Ribeira, SP, e Alto Vale do Itajaí, SC. O quadro teórico é integrado pela avaliação de políticas públicas, sistema local de inovação e sociologia da tradução. A metodologia utilizada é composta por análise de documentos oficiais, jornais, entrevistas com atores-chave e aplicação de questionários. As trajetórias da piscicultura e da ocupação dos territórios foram descritas e analisadas historicamente. As dinâmicas de desenvolvimento da piscicultura foram abordadas considerando um sistema local de inovação integrado por quatro pólos de competência: produção, formação, ciência e financiamento, que foi assimilado como a rede sociotécnica da atividade. A hipótese foi confirmada, ou seja, a capacidade de inovação da piscicultura é determinada pela interação dos quatro pólos e as políticas públicas estão presentes em três, sendo um fator determinante para a durabilidade da prática da atividade. No Vale do Ribeira as coordenações entre os atores da rede foram comerciais e as ações governamentais, fundamentalmente, foram realizadas em infra-estrutura e situadas fora da rede sociotécnica, que teve baixa capacidade de reação diante da crise econômica da piscicultura. No Alto Vale do Itajaí, as ações governamentais foram, principalmente, em pesquisa e formação que, em interação com a significativa organização dos atores da rede determinada pelas proximidades cultural, geográfica e social, proporcionaram grande capacidade de reação às crises experimentadas e, conseqüentemente, durabilidade à prática da piscicultura
Keywords: Aquicultura; Peixe - Criação; Políticas públicas; Economia; Ocupações; Fishes